تطوير المعجم العربي الملايوي التعليمي الثنائي للطلاب في المدراس الماليزية = The Development of Arabic-Malay bilingual dictionaries for Malaysian school students - Abd Rahman, Lubna; Dollah, Nafi@Hanafi (USIM Press, Universiti Sains Islam Malaysia (USIM), 2016)
This research explores the development of the Malaysian primary and secondary school students’ Arabic-Malay dictionaries in terms of its lexical entries and definitions. In meeting the objective of bilingual dictionary education in Malaysia, this research has adopted the analytical method. Three Arabic-Malay bilingual dictionaries selected for analysis, namely; “Al Marbawi” Dictionary (Kamus al Marbawi), “Oxford Fajar” Dictionary (Oxford Fajar) and Al Mukhtar Dictionary (Kamus al Mukhtar) have been examined thoroughly via the process of dissecting the vocabulary entries and analysing the definition and problems associated with them (semantics). In addition, further explication on the exact vocabulary entries (definitions, accuracy, adequacy), as well as the ability and competency of affected users was also conducted. The selection of the three aforementioned dictionaries is not just for comparison, but to ascertain their content and lexical entries for further improvement and enhancement. Due to the complex nature of its entries, it is observed that a large number of Malay-Arabic learners are not acquainted with the use of these bilingual dictionaries as means of enhancing their language skills. Since vocabulary is an important element in the study of language, it is pertinent that a study on ways of facilitating the process of vocabulary acquisition is conducted using the analytical method of the bilingual dictionaries.